Exploration Of Students' and Lecturers' Perceptions Towards the Utilization of Generative Artificial Intelligence - Ardian Pitra Satya Purnama; Tomy Kartika Putra; Adip Arifin; Shofie Azizah (Journal of English Language Learning, 2024)
The development of artificial intelligence (AI) tools such as Perplexity AI has been shown to improve self-confidence, academic achievement, and motivation to learn. This study aims to determine the understanding, benefits, challenges, and application of generative AI (GenAI) in education. Mixed research methods were used, with surveys and interviews involving students from Jenderal Soedirman University and Widya Mandala University. Results showed that most students understood and recognized the benefits of Perplexity AI in lectures, despite concerns over ethics, human interaction, and technology management. The implications of this study emphasize the importance of in-depth learning about the principles and ethics of AI use as well as the need for clear standards to ensure the responsible use of AI in education.